A Randomized controlled clinical trial on dose optimization of thalidomide in maintenance treatment for recurrent aphthous stomatitis. (19th November 2021) - Deng, Yiwen; Wei, Wei; Wang, Yufeng; Pan, Lei; Du, Guanhuan; Yao, Hui; Tang, Guoyao
Abstract: Background: Recurrent aphthous stomatitis (RAS) is the most common oral mucosal disease, and ulcer‐free periods are a major concern for patients. Thalidomide has been shown to be an effective systemic drug in the treatment of RAS, but the value of undertaking a trial to evaluate various maintenance doses was warranted. Methods: We performed this randomized controlled clinical trial with a two‐stage design. Firstly, all the 125 cases of RAS received prednisone at a starting dose of 15 mg/d for one week as an initial therapeutic drug. Secondly, the 100 cases of RAS in the experimental group received thalidomide (50 mg/d vs. 25 mg/d) as a maintenance drug to observe its efficacy and safety. Results: During maintenance medication at the fourth and eighth weekend, the two doses (50 and 25 mg/d) of thalidomide were equivalent in reducing the incidence of ulcers, ulcer number, and ulcer pain, respectively (all p  > 0.05). Notably, the ulcer‐free period in the group using 25 mg/d thalidomide for eight weeks was longer (mean, >3 months) than those in the other groups (all p  < 0.05). Importantly, the total adverse events in the group using 25 mg/d thalidomide were significantly less than those in the group using 50 mg/d ( p  < 0.001). Moreover, the effect of 50 mg/d thalidomide on the levels of various salivary cytokines was not superior to 25 mg/d medication ( p  > 0.05). Conclusion: This dose optimization study concluded that 25 mg/d thalidomide had a long‐term effect on extending the recurrence interval of RAS with better safety.